The Effect of Kegel Exercises on Urinary Incontinence in the Elderly at UPT Panti Sosial Tresna Werdha Glenmore - Aprilyawan, Grenda; Makrup, Makrup; Wulandari, Enny (Griya Eka Sejahtera, 2025)
Background: The aging process is a natural process of life that occurs from the beginning of a person's life, with several phases, namely childhood, adulthood, and old age. The elderly can experience various changes including physical, psychosocial, and spiritual changes. One of the physiological changes that occurs in the elderly is a decrease in urethral muscle tension due to a decrease in the hormone estrogen which causes urinary incontinence. Urinary incontinence is the involuntary discharge of urine (unconscious or bedwetting) at an inappropriate time and place outside of desire. This study aimed to analyze the effect of Kegel exercises on urinary incontinence in the elderly.Methods: The research design used was pre-experimental with a one group pre-test post-test design. The population of this study was all elderly people who experienced urinary incontinence at the UPT Panti Sosial Tresna Werdha Glenmore, this study was conducted on 34 elderly people. The sampling technique in this study used Nonprobability Sampling, namely using Saturated Sampling (total sampling). Data collection used a questionnaire sheet. The data obtained were then coded, scored, tabulated, and analyzed using the Wilcoxon test with a significant value of 0.05.Results: The results of this study show the results of p-value (0.000) ≤ α (0.05) which means that there is an effect of Kegel exercises on urinary incontinence in the elderly at UPT Panti Sosial Tresna Wherda Glenmore.Conclusion: Based on these results, it can be concluded that Kegel exercises can increase the strength of the pelvic floor muscles in urinary incontinence conditions. So it can be used as a non-pharmacological therapy for the elderly who experience urinary incontinence at UPT Panti Sosial Tresna Wherda Glenmore